Malaysian Islamic banks performance vs. internal and external characteristics - Salawati, Sahari; Nurain Khairunnisa, Ubaidillah (Penerbit Akademia baru, 2017)
Journal of Advanced Research in Business and Management Studies 9, Issue 1 (2017) 45-53